2009
DOI: 10.1104/pp.108.131714
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of Physcomitrella patens Desiccation Tolerance through a Proteomic Strategy    

Abstract: The moss Physcomitrella patens has been shown to tolerate abiotic stresses, including salinity, cold, and desiccation. To better understand this plant's mechanism of desiccation tolerance, we have applied cellular and proteomic analyses. Gametophores were desiccated over 1 month to 10% of their original fresh weight. We report that during the course of dehydration, several related processes are set in motion: plasmolysis, chloroplast remodeling, and microtubule depolymerization. Despite the severe desiccation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 66 publications
6
121
0
2
Order By: Relevance
“…Water contents in this study are expressed on a dry matter basis, which reflects how much water remains to solvate and separate cellular contents, rather than the extent of water lost from the original hydrated tissue. In contrast, most previous studies of the dehydration tolerance of Physcomitrella have reported water loss in terms of fresh weight (Cuming et al 2007;Frank et al 2005;Pressel and Duckett 2010;Saavedra et al 2006;Wang et al 2009), which is common for measures of drought tolerance, but which may be less useful for studies of moss, whose fresh weight may include significant, but variable, amounts of surface water. In our studies, the initial water content of the colonies varied extensively; therefore, water losses corresponding to 90% of the fresh weight could leave from 0.2 to 2 g g dm -1 water remaining in the sample (e.g.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Water contents in this study are expressed on a dry matter basis, which reflects how much water remains to solvate and separate cellular contents, rather than the extent of water lost from the original hydrated tissue. In contrast, most previous studies of the dehydration tolerance of Physcomitrella have reported water loss in terms of fresh weight (Cuming et al 2007;Frank et al 2005;Pressel and Duckett 2010;Saavedra et al 2006;Wang et al 2009), which is common for measures of drought tolerance, but which may be less useful for studies of moss, whose fresh weight may include significant, but variable, amounts of surface water. In our studies, the initial water content of the colonies varied extensively; therefore, water losses corresponding to 90% of the fresh weight could leave from 0.2 to 2 g g dm -1 water remaining in the sample (e.g.…”
Section: Discussionmentioning
confidence: 66%
“…Desiccation tolerant cells survive the loss of all bulk water, plus the loss of interfacial water associated with macromolecular surfaces; this generally occurs at water contents less than about 0.1-0.3 g g dm -1 (dry matter) (Alpert 2005;Hoekstra et al 2001), although the precise value depends upon the composition of the cells (Walters and Koster 2007). Given these standard definitions, the description of Physcomitrella as desiccation tolerant (Wang et al 2009) merits closer investigation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Plants make adjustment at different levels of organization (molecular, cellular, tissue, organ, system, anatomical, morphological) to cope with stresses (Atkinson and Urwin 2012 ). Signaling and regulatory (transcription factors, phosphatases, kinases) mechanisms get activated under stress (Krasensky and Jonak 2012 ;Wang et al 2009 ). Various signaling processes involving calcium (Pan et al 2012 ;Reddy et al 2011 ), ROS (Ahmad et al 2010 ;Loiacono and De Tullio 2012 ), and kinase cascades (Baena-Gonzalez and Sheen 2008 ) are induced for signal transduction.…”
Section: Metabolic Tuning In Plants In Response To Abiotic Stressesmentioning
confidence: 99%
“…Protein spots were manually excised from the gel and ingel digestion by trypsin (Promega, Madison, WI, USA) was performed using the method of Wang et al (2009) with minor modifications. Gel slices were washed with 25% (v/v) ethanol and 7% (v/v) acetic acid for 12 h at room temperature, and destained with 50 mM NH 4 HCO 3 in 50% (v/v) methanol for 1 h at 40°C.…”
Section: In-gel Digestion and Protein Identificationmentioning
confidence: 99%